ENSURING RACIAL AND CULTURAL DIVERSITY, SUSTAINABILITY AND EQUALITY IN SPORTS (Academicia Globe: Inderscience Research, 2025)
This article will address issues of racial and cultural diversity, sustainability and equality in sports. While there have been cases of discrimination and social inequality in sports at the time, today a number of initiatives are underway to promote racial and cultural diversity as well as make the sport accessible to all strata. The article emphasizes the need to promote stability and mutual respect in society by ensuring equality in sports.